Identifikasi Dan Uji Kandungan Metabolit Sekunder Tumbuhan Obat - Ridwan Ridwan; La Ode Kaharudin (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2022)
Medicinal plants are an important, easily accessible resource for use as health care for rural communities. Medicinal plants are an important, easily accessible resource for use as health care for rural communities. The study uses plant samples that have been used by the people of North Buton as traditional medicine for generations. This study aims to determine the types of medicinal plants and the content of secondary metabolites contained in these plants. The research was carried out through several stages including: identification stage, then the secondary metabolite content test stage which was analyzed through several stages, namely extraction, flavonoid test, alkaloid test, steroid/terpenoid test, tannin test, saponin test and phenol test. The content of secondary metabolites was tested on three parts of plant organs, namely roots, stems and leaves. The results showed that the plants used were the species Embelia sp. and Tetracera indica (Christm. & panz. Merr.). Furthermore, the secondary metabolite test results showed that Embelia sp. contains alkaloids, flavonoids, terpenoids, tannins, and phenols. The roots, stems and leaves of Tetracera indica (Christm. & panz. Merr.) contain alkaloids, terpenoids, saponins, tannins, and phenols.